Public and private sectors collective response to combat COVID-19 in Malaysia - Ching Siang Tan; Saim Lokman; Yao Rao; Szu Hua Kok; Long Chiau Ming (Taylor & Francis Group, 2021)
Over the last year, the dangerous severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread rapidly around the world. Malaysia has not been excluded from this COVID-19 pandemic. The resurgence of COVID-19 cases has overwhelmed the public healthcare system and overloaded the healthcare resources. Ministry of Health (MOH) Malaysia has adopted an Emergency Ordinance (EO) to instruct private hospitals to receive both COVID-19 and non-COVID-19 patients to reduce the strain on public facilities. The treatment of COVID-19 patients at private hospitals could help to boost the bed and critical care occupancy. However, with the absence of insurance coverage because COVID-19 is categorised as pandemic-related diseases, there are some challenges and opportunities posed by the treatment fees management. Another major issue in the collaboration between public and private hospitals is the willingness of private medical consultants to participate in the management of COVID-19 patients, because medical consultants in private hospitals in Malaysia are not hospital employees, but what are termed "private contractors" who provide patient care services to the hospitals. Other collaborative measures with private healthcare providers, e.g. tele-conferencing by private medical clinics to monitor COVID-19 patients and the rollout of national vaccination programme. The public and private healthcare partnership must be enhanced, and continue to find effective ways to collaborate further to combat the pandemic. The MOH, private healthcare sectors and insurance providers need to have a synergistic COVID-19 treatment plans to ensure public as well as insurance policy holders have equal opportunities for COVID-19 screening tests, vaccinations and treatment.